2021
DOI: 10.2166/hydro.2021.126
|View full text |Cite
|
Sign up to set email alerts
|

Experiments of an IoT-based wireless sensor network for flood monitoring in Colima, Mexico

Abstract: Urban flooding is one of the major issues in many parts of the world, and its management is often challenging. One of the challenges highlighted by the hydrology and related communities is the need for more open data and monitoring of floods in space and time. In this paper, we present the development phases and experiments of an Internet of Things (IoT)-based wireless sensor network for hydrometeorological data collection and flood monitoring for the urban area of Colima-Villa de Álvarez in Mexico. The networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…An IoT-based WSN for hydrometeorological data collecting and flood monitoring for the urban region of Colima-Villa de lvarez in Mexico was developed and tested by Mendoza-Cano et al [76], IoT message queuing telemetry transport protocol is used to transport real-time fluvial water level, soil moisture, and weather data to the server and a web application using 3G and Wi-Fi networks. When tropical storms strike, it is clear that the smart water network is capable of gathering hydrometeorological data in real time.…”
Section: Other Applications Of Iot Based Wsnmentioning
confidence: 99%
“…An IoT-based WSN for hydrometeorological data collecting and flood monitoring for the urban region of Colima-Villa de lvarez in Mexico was developed and tested by Mendoza-Cano et al [76], IoT message queuing telemetry transport protocol is used to transport real-time fluvial water level, soil moisture, and weather data to the server and a web application using 3G and Wi-Fi networks. When tropical storms strike, it is clear that the smart water network is capable of gathering hydrometeorological data in real time.…”
Section: Other Applications Of Iot Based Wsnmentioning
confidence: 99%
“…Kong, et al [52] have reviewed the major applications of big data in urban sustainability and identified that this technology is mainly applied in resource and environment-related areas, such as urban land use and planning, resources and energy utilization, and environmental sustainability. Mendoza-Cano, et al [15] proposed an IoT-based wireless sensor network to collect real-time data for flood monitoring. Smart water management is expected to solve sustainability challenges such as water overuse, flood and drought, and pollution [17].…”
Section: Digital Technologies Implementation In the Water And Wastewater Sectormentioning
confidence: 99%
“…The sludge wastewater treatment process, for example, can be monitored by digital image processing [53]. IoT monitoring can be applied in various scenarios, including real-time river water quality, in-pipe water quality, hydrometeorological and flood data, and water demand data in commercial buildings [13][14][15][16].…”
Section: Digital Technologies Implementation In the Water And Wastewater Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…flood 6 and avalanche 7 monitoring. Although satellite-derived imagery has long been used for Earth observations, it is now being used in innovative ways.…”
mentioning
confidence: 99%